Flood Risk and Insurance Take-up in the Flood Zone and Its Periphery - Ivan Petkov; Francesc Ortega (Institute of Labor Economics (IZA), 2024)
Many studies have investigated flood risk and insurance coverage in the 100-year flood zone, but much less is known about the periphery of the flood zone. We present a new approach to estimate flood risk and insurance take-up in the vicinity of the flood zone based on building-level inundation data. We illustrate our approach using data for New York after hurricane Sandy. We show that flood risk falls rapidly as we move away from the flood zone, but remains fairly high for properties located within 250 meters of the flood zone. We also document substantial voluntary insurance take-up in this area prior to the storm, reflecting homeowners' perception of flood risk. Next, we show that experiencing flooding during Sandy led to large increases in flood insurance coverage in the flood zone and its periphery. But, while in the flood zone the increase vanished after 3 years, it was highly persistent in the periphery. By using information on the types of insurance policies purchased by homeowners, we provide evidence that strongly suggests that periphery residents who experienced flooding revised upwardly their beliefs about flood risk and adapted by purchasing (affordable) flood insurance.
Keywords: Q54; G22; 330; flood risk; flood insurance; FEMA; NFIP; hurricane Sandy